Tectonic, diapiric and sedimentary chaotic rocks of the Rakhine coast, western Myanmar - Moore, G. F. (2021)
The western margin of Myanmar is the northern extension the active Sunda (India-Eurasia) subduction zone. Coastal regions and offshore islands have remarkable exposures of chaotic rock terranes along wave-cut terraces that allow characteristics of tectonic, sedimentary and diapiric mélanges to be recognized. Tectonic shear zones (tectonic mélanges) contain fragments of Cretaceous ophiolites (chrome-spinel-bearing peridotites and radiolarian cherts) that are in contact with thrust packets of Eocene turbidite units (broken formations). The turbidites contain shale-rich beds that have been sheared during soft-sediment deformation (sedimentary broken formations) and are sandwiched between undeformed thick sandy beds. These are mass transport deposits (MTDs) that most likely formed during deposition of the initial detritus of the Himalayan orogenic zone, probably trench slope basins on the accretionary prism. The ophiolitic and turbiditic thrust slices have been exhumed and are currently being intruded by active mud volcanoes that bring fragments of units up from depth to the surface, forming diapiric mélanges. These diapiric mélange bodies contain only small fragments (<50 cm) that are randomly oriented and do not exhibit shear fabrics. Because the region lacks superimposed deformation characteristic of most orogenic belts, the origins of all three rock bodies can easily be distinguished.